Pengaruh pembelajaran berbasis moodle sanggar belajar dengan pendekatan TPACK terhadap hasil belajar siswa SMA - Edy, Syifaurrohmah Kusuma; Nindiasari, Hepsi (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2023)
In the 21st century learning must be integrated with various technological devices in the entire process, this also supports the industrial revolution 4.0 program. The TPACK approach is the answer to these demands, where learning is based on knowledge of teaching materials (content knowledge), how to teach material (pedagogical knowledge), and knowledge of how to use technology (technological knowledge). One example of the application of technology in learning is the Modular Object Oriented Dynamic Learning Environment (moodle), at the research site, namely SMAN 8 Serang City, there is a moodle-based learning studio website. The sample of this study were students of class X at SMAN 8 Kota Serang. The research method used in this study was quantitative pre-experimental design, with a one-group pretest-posttest research design. The results of the study showed that there was an increase in the learning outcomes of students who had studied using the moodle sanggar belajar by 52.3%. The n-gain score obtained was 61.62% which was categorized as